Water refilling along vessels at initial stage of willow cuttage revealed by move contrast CT - Xu, Mingwei; Li, Ke; Xue, Yanling; Wang, Feixiang; Liu, Zhixuan; Song, Zenghao; Xiao, Tiqiao (Frontiers in Physics, 2023)
Cuttage is a widely used technique for plant propagation, whose success relies on the refilling for water transport recovery. However, requirements for refilling characterization studies, including large penetration depth, fast temporal resolution and high spatial resolution, cannot be reached simultaneously via conventional imaging techniques. So far, the dynamic process of water refilling along the microvessels at the initial stage of cuttage, as well as its characteristics, remains unclear. Hereby, we developed a move-contrast X-ray microtomography method which achieves 3D dynamic non-destructive imaging of water refilling at the initial stage of willow branch cuttage, without the aid of any contrast agent. Experimental results indicate three primary refilling modalities in microvessels: 1) the osmosis type, mainly manifested by the osmosis of tissue through the vessel wall into the cavity; 2) the linear type, revealed as the tissue permeates to a certain extent where the liquid column in the microvessels is completely formed; and 3) an osmosis-linear mixed type refilling as an intermediate state. Further analysis also exhibits a "temporal-spatial relay" mode of refilling between adjacent vessels. Since the vessel length is quite limited, the cavitation and the relay refilling mode of microvessels can be an important way to achieve long-distance water transport.